Distinctive numbers of production systems functioning description - Pignasty, O.M. (Вопросы атомной науки и техники, 2007)
The production system of an enterprise is represented as the system with large quantity of elements, which are the objects of one's labour. The distinctive numbers of the production system are introduced by means of statistical mechanics. This approach gives the possibility of qualitative estimation of production processes functioning, sound selection of the corresponding equations set of macroscopic parameters balances for description of real production object. The estimation of the model selection should be interpreted as the qualitative one. The approach has the advantage of easy comparison of the results, corresponding to different microscopic models.